Seven years analysis of postpartum death in Selangor, Malaysia: a lesson learnt - B, Nor Izyani; A, Norfazilah; HA, Siti Harirotul; R, Nur Shazleen Nisha; D, Faiz (Penerbit Universiti Kebangsaan Malaysia, 2023)
Information on determinants of postpartum death enhances understanding of the fundamental causes of mortality. Studies on postpartum death in Malaysia are limited despite increasing trends of postpartum mortality. This study aimed to ascertain the determinants of postpartum death in Selangor, Malaysia. A case control was conducted using data from the Maternal Death Registry, Selangor State Health Department, Malaysia. A total of 144 postpartum death cases were included for analysis after the removal of fortuitous and unknown death. Controls were mothers who survived six weeks after childbirth and were selected via simple random sampling. The odds of postpartum death among multiparous was almost two times higher (aOR; 1.76 95% CI 1.10,2.82). The presence of pre-existing medical or surgical problems were associated with a three-folds increase in the odds of postpartum death (aOR 3.23; 95% CI 1.91,5.47). The odds of postpartum death were ten times higher for those who gave birth in non-health facilities (aOR 10.62; 95% CI 2.64,42.74). Women who underwent caesarean section had almost three times more odds (aOR 2.50; 95% CI 1.60,3.91) for death. Women who received antenatal care in government health facilities had low odds (aOR 0.34; 95% CI 0.19,0.60) for postpartum death. The determinants showed significant association with postpartum death in Selangor, Malaysia which included the presence of pre-existing medical or surgical illness, place of birth, mode of birth, place of antenatal care and Malaysian ethnicity-citizenship. In the future, health programmes should not only aim to reduce postpartum deaths by emphasising maternal education and empowerment, but should also enhance pre-pregnancy care, provide continual obstetric emergency skill training to healthcare providers, collaborate with several agencies and underwrite migrants’ maternal healthcare fees.